Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1103/physrevb.91.165403
|View full text |Cite
|
Sign up to set email alerts
|

Observation of interlayer phonon modes in van der Waals heterostructures

Abstract: Abstract:We have investigated the vibrational properties of van der Waals heterostructures of monolayer transition metal dichalcogenides (TMDs), specifically MoS 2 /WSe 2 and MoSe 2 /MoS 2 heterobilayers as well as twisted MoS 2 bilayers, by means of ultralow-frequency Raman spectroscopy. We discovered Raman features (at 30 ~ 40 cm -1 ) that arise from the layerbreathing mode (LBM) vibrations between the two incommensurate TMD monolayers in these structures. The LBM Raman intensity correlates strongly with the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
200
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(223 citation statements)
references
References 58 publications
(88 reference statements)
19
200
3
Order By: Relevance
“…In order to maintain a sufficient interlayer coupling, careful cleaning of the interface with suitable solvents, annealing procedures or performing the transfer process in inert atmosphere are possible routes. Interlayer coupling in vertical van der Waals heterostructures has been investigated by means of optical spectroscopy with reflectance [162] , photo-luminescence [161,[163][164][165] , electroluminescence [58] , and Raman-experiments [155] , by measurements of the photovoltaic effect [57,60] or by scanning tunneling spectroscopy [166,167] . bound bosonic quasiparticles called interlayer excitons (IX) can form.…”
Section: Optical Properties Of Tmdc Heterostructuresmentioning
confidence: 99%
“…In order to maintain a sufficient interlayer coupling, careful cleaning of the interface with suitable solvents, annealing procedures or performing the transfer process in inert atmosphere are possible routes. Interlayer coupling in vertical van der Waals heterostructures has been investigated by means of optical spectroscopy with reflectance [162] , photo-luminescence [161,[163][164][165] , electroluminescence [58] , and Raman-experiments [155] , by measurements of the photovoltaic effect [57,60] or by scanning tunneling spectroscopy [166,167] . bound bosonic quasiparticles called interlayer excitons (IX) can form.…”
Section: Optical Properties Of Tmdc Heterostructuresmentioning
confidence: 99%
“…[27][28][29] Meanwhile, the manually assembled bilayer generally has an incommensurate lattice structure due to the inevitable interlayer twist and/or lattice constant mismatch. This brings anomalous interlayer couplings which have profound effects on the transport, [14][15][16]30,31 optical 32-36 and Raman 37,38 properties of the bilayers. Moreover, recent theoretical studies have shown that the interlayer coupling together with the formation of a large scale moiré superlattice pattern can lead to the emergence of topological orders in a TMD heterobilayer.…”
Section: 13mentioning
confidence: 99%
“…1c, allows an estimation of the twist angle θ [5,7,[19][20][21][22]. For optical transitions in the parallel band model [19,20], the blue shift, intensity enhancement and width reduction of Raman peaks is attributed to van Hove singularities in the presence of weak interlayer interaction.…”
mentioning
confidence: 99%
“…In spite of subnanometer separation of the van der Waals gap (∼ 0.5 nm), the coupling of the two graphene layers in twisted bilayer graphene (tBLG) varies strongly with temperature (T ), and the twist or misorientation angle θ between the hexagonal lattices of participating graphene layers [1][2][3][4][5][6][7][8][9]. At T Θ BG , where Θ BG is the Bloch-Grüneisen temperature, the layers are coherently coupled either for θ 10…”
mentioning
confidence: 99%
See 1 more Smart Citation